2016
DOI: 10.1007/s00264-016-3275-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arthroscopic techniques on joint volume in shoulder instability: Bankart repair versus capsular shift

Abstract: Purpose The evaluation of glenohumeral joint volume in both unstable (with/without laxity) and stable shoulders (subacromial impingement) and volume reduction potential of arthroscopic techniques: (labral anchor repair vs. capsular shift). Methods Material was based on 133 patients: anterior shoulder instability without laxity (group I, n = 49), with laxity (group II, n = 22) and subacromial impingement (control group, n = 62) operated in 2010-2011. Group I received arthroscopic Bankart repair, group; II -arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
3
9
1
Order By: Relevance
“…Both imaging studies and surgical in vivo studies found pathological capsular enlargements of unstable shoulder joints [ 9 , 10 , 14 , 21 ]. Dewing et al [ 9 ] demonstrated an increased cross-sectional area of the capsule in patients with posterior or multidirectional instability versus controls, as measured by magnetic resonance arthrography [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both imaging studies and surgical in vivo studies found pathological capsular enlargements of unstable shoulder joints [ 9 , 10 , 14 , 21 ]. Dewing et al [ 9 ] demonstrated an increased cross-sectional area of the capsule in patients with posterior or multidirectional instability versus controls, as measured by magnetic resonance arthrography [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This 1.5-mL difference was added to the post-interventional joint volume measurements. A pilot study by Lubiatkowski et al showed that in vivo intraoperative measurement of the shoulder joint volume is a very reliable method with high intraclass correlation coefficients (ICCs), which range from 0.996 to 0.997 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, restoring labral tissue height and shifting of the redundant capsule from the anteroinferior direction should be the final result. 13 Recently, the modified Mason Allen stitch has come into favor and has been theorized to be superior to the simple stitch technique. 9 , 14 , 15 The concept of combining capsular shift and arthroscopic Bankart repair (ABR) with the modified Mason Allen stitch technique has been challenged.…”
Section: Introductionmentioning
confidence: 99%